Analysis of the Village SDGs Model in Remote Village Development in Gorontalo Province - Siske Anani; Ismail Tahir; Frista Iin Wahyuni (Formosa Journal of Sustainable Research, 2022)
The purpose of the current study is to provide knowledge to the community about the management of the potential of the village following the needs of the community, the use of village assets to create added value for some village assets; to increase the original income of the village, net profit/profit that can be an increase in the original income of the village; and to develop the economic resources of the village community. This study was carried out in six stages, namely 1) The preparatory stage includes (a) collection of literature, (b) collection of data and information, and (c) collection of data on the object of study; 2) The analysis phase includes (a) Phenomenon Analysis, (b) Analysis of the Research Focus of the Village SDGs program, and (c) Analysis of Informants; 3) The design stage is to design interview guidelines; 4) Implementation Phase which includes (a) interview process and (b) Documentation collection; 5) Data Analysis Stage which includes (a) Data reduction, (b) Display Data, (c) Drawing conclusions, (d) data validity; and 6) Documentation Stage which includes (a) Report Making and (b) publication of reports. The results of this study show that the implementation of the Pinogu Village SDGs analysis model emphasizes more on the aspects of the realization of activities that have been carried out by the village government. Implementing the Village SDGs program is closely related to village financial management. By implementation of the Village SDGs program by utilizing the use of Village Funds. It is carried out by the Pinogu Village government which refers to the realization of the Village Fund budget